1990
DOI: 10.1152/ajpendo.1990.259.4.e470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise and recovery on muscle protein synthesis in human subjects

Abstract: Previous studies using indirect means to assess the response of protein metabolism to exercise have led to conflicting conclusions. Therefore, in this study we have measured the rate of muscle protein synthesis in normal volunteers at rest, at the end of 4 h of aerobic exercise (40% maximal O2 consumption), and after 4 h of recovery by determining directly the rate of incorporation of 1,2-[13C]leucine into muscle. The rate of muscle protein breakdown was assessed by 3-methylhistidine (3-MH) excretion, and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 1 publication
15
143
0
Order By: Relevance
“…10 completed a session of weight-lifting exercise 2 h prior to the initiation of the tracer infusion experiment. We believe that the prior bout of exercise was the cause of this subject's elevated rate of muscle protein synthesis because (i) Carraro et al 11 have observed an increased rate of muscle protein synthesis during recovery from mild aerobic exercise, and (ii) we have observed an increase in muscle protein synthesis rate in an additional 7 individuals studied in the same manner as those reported here, after a session of resistance exercise (manuscript in Preparation).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…10 completed a session of weight-lifting exercise 2 h prior to the initiation of the tracer infusion experiment. We believe that the prior bout of exercise was the cause of this subject's elevated rate of muscle protein synthesis because (i) Carraro et al 11 have observed an increased rate of muscle protein synthesis during recovery from mild aerobic exercise, and (ii) we have observed an increase in muscle protein synthesis rate in an additional 7 individuals studied in the same manner as those reported here, after a session of resistance exercise (manuscript in Preparation).…”
Section: Resultssupporting
confidence: 67%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] For example, the published values for quadriceps muscle protein synthesis rate in healthy normal subjects are 0.035-0.063% h −1 (SD = 0.009) by Nair et al, 13 0.033-0.064% h −1 (SD = 0.012) by Gibson et al, 1 and 0.036-0.063% h −1 (SD = 0.011) by Nair et al 8 These ranges and standard deviations compare closely with the values reported in the present study (0.023-0.070% h −1 , SD = 0.014) if subject no. 10 is excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, resistance exercise increases protein synthesis [97][98][99][100][101][102][103][104][105][106] and improves protein balance during the recovery phase in the skeletal muscle, 8,107,108 but not during acute bouts of resistance exercise. 109 Similar to resistance exercise, low intensity aerobic training 110 causes a significant increase in fractional synthetic rate in the leg muscle. In contrast, in female deltoid muscle, neither resistance nor swimming exercise, when performed separately, had a significant effect on net muscle protein synthesis, but when combined stimulated increased muscle protein synthesis above baseline levels.…”
Section: A Correspondence Between Immune and Muscle Cellsmentioning
confidence: 99%
“…Each subject underwent a percutaneous biopsy of vastus lateralis before beginning medication and at the end of 8 weeks of treatment. The muscle biopsy was performed after an overnight fast and 2 h of quiet recumbency as previously described (9). Patients were instructed to maintain their prestudy activity and diet programs throughout the 8-week study.…”
Section: Patients and Clinical Protocolmentioning
confidence: 99%